A Letra e o Tempo: a escrita de O. G. Rego de Carvalho entre a ficção e a história da literatura - Fontineles Filho, Pedro Pio (2016)
In 1953 was published the book Ulisses entre o Amor e a Morte, considered the literary debut by Orlando Geraldo Rego de Carvalho. At that time, the publication raised criticism about being treated or not as a book of “Piauiense literature”, whereas it didn’t bring themes taken as regionalists , such as dry, poverty and hunger. Along his trajectory, the author was envolved in other controversy linked to intellectuality, especially to literature, when he said that the “Piauiense literature” didn’t exist. That point of view brought to light, more emphatically, discussions about the status of literature and raised reflections about canon and border issues. Besides that, it expanded parallel discussions about the history of literature, regarding the authorship, biography, production, publication, circulation and reading of the literary texts. The main objective of this study was understand the work of the writter as evidence of the slots inherent in (re) invention and history of the “Piauiense literature”. Time frame that conducted the presente study transited the interstice between 1953 and the early 2000’s. Initial mark refers to the year of literary “debut” of the author, while the final mark takes into account the anthologies and critical fortunes, as well as the educational issues that approach the author’s work and the literary production in general. It’s noteworthy that setbacks and advances on time frame were done, to contemplate relevant aspects to the problematizations, including biographical traits. In this sense, the documentary universe was composed of the books published by the author, notedly Ulisses entre o Amor e a Morte (1953), Rio Subterrâneo (1967), Somos Todos Inocentes (1971) and Como e por que me fiz escritor (1994); books in form of anthologies and critical fortune, that analyze the author’work; article published on internet sites; besides educational issues aimed at students and prepared for college entrance exams. As theoretical and methodological skeleton, it used the propositions by Pierre Bourdieu (2010), Roger Chartier (2014, 2010, 2002) and Michel de Certeau (2011), among others, to think the “literary field” in its different manifestations, since relations of power, as well as the history of literature, of book and of reading. The study considered, thus, that the author’s work is central to the analysis of the relations of power between the Letter and Time, between fiction and the history of literature.